Blog mix 2014 - Språkbanken Text (University of Gothenburg, 2024)
Material from a selection of Swedish blogs. Is updated regularly.

Material från ett urval av svenska bloggar. Uppdateras regelbundet.
Bloggmix 2014
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik